ADVANTAGES OF USING PROJECT-BASED METHODOLOGY IN EDUCATIONAL PROCESS (Scientific journal of the Fergana State University, 2023)
While teaching the use of modern teaching technologies, a  project-based method is  an important factor in improving the quality and efficiency of education. This scientific thesis is devoted to the project-based  learning in the educational process.